The Relationship Between Boredom Proneness And Problematic Smartphone Use Among Adolescents - Dillvia Nadilla Putri; Nurul Aiyuda; Risca Aulia (CV. Era Digital Nusantara, 2026)
Adolescents are an age group with high levels of smartphone use, making them susceptible to problematic smartphone use. One psychological factor believed to play a role in this condition is boredom proneness, which is an individual’s tendency to become easily bored. Adolescents with high levels of boredom tend to use smartphones as a means of distraction, which, if uncontrolled, can have a negative impact on daily activities. This study aims to determine the relationship between boredom proneness and problematic smartphone use among adolescents in Indonesia. A quantitative correlational approach was used. The sample consisted of 280 adolescents aged 12–18 years, comprising 214 females and 66 males, selected via purposive sampling. The research instruments used were the Short Boredom Proneness Scale and the Smartphone Addiction Scale–Short Version. Data were analyzed using the Pearson Product-Moment correlation test. The results of the analysis indicated a significant positive relationship between boredom proneness and problematic smartphone use, with a correlation coefficient of r = .693 and a significance level of p < .05. These findings suggest that the higher the level of boredom proneness among adolescents, the higher the level of problematic smartphone use. Thus, boredom proneness is one of the psychological factors contributing to the emergence of problematic smartphone use among adolescents.